Literature Review : Efektifitas Senam Kaki terhadap Nilai Ankle Brachial Index (ABI) pada Pasien Diabetes Melitus Tipe 2: Literature Review : Effectiveness of Foot Exercise on the Value of Ankle Brachial Index (ABI) in Type 2 Diabetes Mellitus Patients - Elsa Gabriella Mustika; Indah Puspitasari; Ponirah Ponirah (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Background: Diabetes is a serious long-term condition that significantly impacts the lives and well-being of individuals, families, and communities worldwide. Purpose: This literature review aims to describe the effectiveness of foot exercises on the value of the Ankle Brachial Index (ABI) in Type 2 Diabetes Mellitus patients. Purpose: This literature review aims to describe the effectiveness of foot exercises on the value of the Ankle Brachial Index (ABI) in Type 2 Diabetes Mellitus patients. Methods: This scientific paper is a literature review search using an electronic database: Google Scholar, Semantic Scholar, and Pubmed. The keywords used in the search are Diabetes Mellitus Type 2 or Diabetes Mellitus Type 2, Foot exercise or Foot exercise, and Ankle Brachial Index or Ankle Brachial Index. The inclusion criteria used in the article are accessible full-text manuscripts, in English and Indonesian, free of charge, the journal year used is limited to the last 10 years, the results are found each 1 article from Semantic Scholar and 3 Google Scholar, from 4 articles discussing the effectiveness of foot exercise on the value of the ankle-brachial index in patients with type 2 diabetes mellitus. Results: The analysis of 4 articles showed an increase in value; the most effective research was in Wahyuni's research in 2016, conducted within 3 days with an increase in value of 0.31. Conclusion: In reviewing this literature review, it can be concluded that the effectiveness of foot exercises on the value of the Ankle Brachial Index in Type 2 Diabetes Mellitus patients.